Bullying Prevention Program Since Elementary School in Peguyangan Kaja Village, Denpasar - SANCAYA, I Wayan Werasmana (Community Services: Sustainability Development, 2025)
This community service program discusses a bullying prevention program at an Elementary School in Peguyangan Kaja Village, Denpasar, which aims to increase students, teachers, and parents' awareness of the negative impacts of bullying on child development. Bullying can damage mental and social health, so it requires comprehensive educational intervention. The program successfully increased students' understanding of bullying from 45% to 85% through interactive approaches such as simulations and role-playing. Parent and teacher involvement was also strengthened through training that provided insight into how to detect and handle bullying situations. In addition, one school successfully developed a clear anti-bullying policy, including reporting and handling mechanisms. Although the program showed positive results, there were still challenges, such as students' perceptions of joking as bullying and parents' limited time to get involved. Therefore, ongoing support is needed from all parties to create a safe and harmonious learning environment. This program proves the importance of collaboration between schools, families, and the community in addressing bullying problems for optimal child development. Through ongoing education, it is hoped that bullying can be reduced and students' characters can be formed positively.